Radiological Protection Policy Aspects concerning the Design and Operation Modus of Medium Energy (< 1 GeV) or High Current (> 25 MeV, = 1 kA) Electron Accelerators Facilities - Spyropoulos, B. (HNPS Advances in Nuclear Physics, 2019)
Radiation Protection in major research-facilities includes several aspects concerning their planning, the hazard-sources, the environmental protection and the general safety. The present paper includes a concise presentation of the approach to the radiation protection policies proposed for the Athens Race Track Microtron (250 MeV, 550 mA) and the Heraclion Modified Betatron Accelerator (25 MeV, 1 kA).